2013
DOI: 10.5194/bg-10-4641-2013
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of methane in the Lena Delta and Buor-Khaya Bay, Russia

Abstract: The Lena River is one of the largest Russian rivers draining into the Laptev Sea. The permafrost areas surrounding the Lena are predicted to thaw at increasing rates due to global temperature increases. With this thawing, large amounts of carbon – either organic or in the gaseous forms carbon dioxide and methane – will reach the waters of the Lena and the adjacent Buor-Khaya Bay (Laptev Sea). Methane concentrations and the isotopic signal of methane in the waters of the Lena Delta and estuary were monitored fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 54 publications
6
43
1
Order By: Relevance
“…The observed concentrations of CH 4 in the Lena River, delta and estuary vary considerably in magnitude and are observed to decrease from the river towards the open sea, probably due to outgassing from the supersaturated river water to the atmosphere Semiletov et al, 2011Semiletov et al, , 2012Bussmann, 2013). Hence, the role of riverine CH 4 loads for the CH 4 concentration in the Laptev Sea is unsolved, in particular if the permafrost in the catchment area of the Lena River thaws and large amounts of carbon reach the coastal zone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The observed concentrations of CH 4 in the Lena River, delta and estuary vary considerably in magnitude and are observed to decrease from the river towards the open sea, probably due to outgassing from the supersaturated river water to the atmosphere Semiletov et al, 2011Semiletov et al, , 2012Bussmann, 2013). Hence, the role of riverine CH 4 loads for the CH 4 concentration in the Laptev Sea is unsolved, in particular if the permafrost in the catchment area of the Lena River thaws and large amounts of carbon reach the coastal zone.…”
Section: Discussionmentioning
confidence: 99%
“…Although the constant oxidation rate is a simplification, this approach was applied to investigate how different observed rates affect the seaÁair exchange. The concentration of CH 4 in the river water was set to 20 nmol L (1 , which is the upper limit from observations of Semiletov et al (2011), but the value is in the lower part observed by Bussmann (2013). The flux from the sediment was taken from Shakhova et al (2005) and the atmospheric pCH 4 values were downloaded data from the National Oceanic and atmospheric Administration (NOAA), Point Barrow, Alaska http://www.esrl.noaa.gov/gmd/ dv/iadv/graph.php?code0BRW&program0ccgg&type0ts (Dlugokencky et al, 2012).…”
Section: Sensitivity Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…But while coastal erosion and fluvial transports of particulate as well as dissolved organic carbon into the Buor-Khaya Gulf (Charkin et al, 2011) are normal processes, the expected increase in discharge resulting from permafrost thaw is also likely to lead to a considerable increase in delivery of inorganic nutrients (Nowinski et al, 2008), terrigenous dissolved organic carbon (DOC) and particulate organic carbon (POC) as well as methane to coastal waters (Finlay et al, 2006;Bussmann, 2013). Changes in these parameters could also have profound consequences for the resident phytoplankton communities.…”
Section: Introductionmentioning
confidence: 99%